The making of a story : a Norton guide to creative writing - LaPlante, Alice, 1958- (New York : W.W. Norton, 2007)
A guide to creative writing that introduces readers to each stage of the creative writing process and helps them build their writing skills through exercises and real-life examples.
ch. 13. Learning to fail better -- pt. 1. On revision -- Getting started -- Advice for writers from writers -- Perfection is our enemy -- The workshop method -- Undue influence : a cautionary tale -- The developmental stages of a creative work -- "Hot spots" and other noteworthy aspects of an early draft -- An exercise-based approach to deep revision -- A word about constraints -- pt. 2. Exercises -- Analytical/mechanical exercises -- Creative exercises -- Research-based exercises -- Chance-based exercises -- Revision example : "The company of men" / Jan Ellison -- pt. 3. Reading as a writer -- "Shitty first drafts" / Anne Lamott -- "The Carver chronicles" / D.T. Max -- "The bath" / Raymond Carver -- "A small, good thing" / Raymond Carver -- ch. 14. Getting beyond facts to truth -- pt. 1. Some final thoughts on creative nonfiction -- Getting started -- Just the facts, ma'am -- Recollections and re-creations -- Ethical considerations -- Subjectivity vs. objectivity -- A trip of self-discovery -- To be in or out of the story? -- pt. 2. Reading as a writer -- "Learning to drive" / Katha Pollitt -- Glossary-- Bibliography -- List of stories -- Permissions -- Index.
Includes bibliographical references (p. 647-655) and index.
Keywords: English language -- Rhetoric -- Handbooks, manuals, etc; English language -- Style -- Handbooks, manuals, etc; Creative writing -- Handbooks, manuals, etc; Report writing -- Handbooks, manuals, etc